Effect of Rectal Misoprostol in Reducing Intra-Operative Blood Loss During Myomectomy - A Randomized Controlled Trial - Nisar, Salma; Qarni, Muhammad Awais; Nisar, Sarah; Mumtaz, Sadaf; Muhammad, Ammara Iqbal; Zaheer, Qasim (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the effect of administration of pre-operative rectal misoprostol in reducing intra-operative blood loss during abdominal myomectomy in comparison to no treatment. Study design: Randomized controlled trial (single blind) (NCT05108597 at Clinicaltrials.gov) Place and Duration of the Study: Obstetrics and Gynecology department, Pak Emirates Military Hospital, Rawalpindi from March 2019 to March 2020. Methodology: A total of 200 women for elective abdominal myomectomy were randomly allocated into two groups. In the experimental group, 100 women were administered 400ug Misoprostol through the rectal route prior to surgery and 100 were in the control group, in which no drug was administered. The surgical procedural elements, the surgeon or surgeons performing the procedure and the use of antibiotics as well as anesthetic agents was standardized to remove any bias. Intraoperative blood loss was recorded by a single trained doctor and calculated using visual scale for the abdominal sponges and chest swabs/gauzes used during surgery and blood collected in suction bottle. Results: The mean age was 30.45±4.58 years. The mean blood loss was significantly low in experimental groups as compare to control groups [523±97.3 vs. 815.9±117.93 p<0.001] Conclusion: In conclusion, administration of rectal misoprostol appears to be effective in reducing intra-abdominal blood loss during abdominal myomectomy.